RELATIONSHIP BETWEEN HOSTEL ACCOMMODATION AND MANAGERIAL EFFECTIVENESS IN FEDERAL UNIVERSITIES IN NORTH WEST ZONE, NIGERIA - ABDULLAHI, SAFINA JANTULLU; KWASHABAWA, BALA BAKWAI (Sokoto Educational Review, 2025)
This study investigates the relationship between hostel accommodation and managerial effectiveness in federal universities in North West, Nigeria. The objectives were to determine the extent of hostel accommodation management and to ascertain the level of managerial effectiveness in these institutions. The research employed a descriptive survey of a correlational type. The study’s population was 4,736 individuals, comprising 20 management staff, 25 non-academic staff, and 4,691 students. A sample of 357 was selected using the Research Advisors Table (2006). Two instruments were used: the Management of School Hostel Accommodation Rating Scale (MSHARS) and the Managerial Effectiveness Questionnaire (MEQ). Their reliability indices were 0.75 and 0.76, respectively, obtained through a test-retest method. Data were analyzed using percentages to answer the research questions, while the Pearson Product-Moment Correlation (PPMC) was used to test the hypothesis at a 0.05 level of significance. The study found a low level of hostel accommodation management in the universities surveyed. It is therefore recommended that university management improve the provision of adequate hostel accommodation and modern facilities to meet students’ needs. DOI: https://doie.org/10.10318/SER.2025191358